Composting as sustainable strategy for municipal solid waste management in the Chimborazo Region, Ecuador: Suitability of the obtained composts for seedling production. (10th January 2017) - Jara-Samaniego, J.; Pérez-Murcia, M.D.; Bustamante, M.A.; Pérez-Espinosa, A.; Paredes, C.; López, M.; López-Lluch, D.B.; Gavilanes-Terán, I.; Moral, R.
Abstract: Solid waste management is a huge challenge in developing countries mainly due to factors such as population increase, poverty and the lack of proper investment by the respective governments. Composting, if it is properly carried out, can constitute a viable method for organic waste management in these countries, due to its low operational cost and the income generation, with low environmental impact. Thus, this paper studies composting as treatment method for the sustainable management and recycling of the municipal solid wastes generated in the Chimborazo Region (Ecuador), and the use of some of the composts obtained as growing media for seedling production. For this, six piles were elaborated using municipal solid wastes: Piles 1, 2 and 3 were prepared using municipal solid wastes from the Riobamba landfill and Piles 4, 5 and 6 were elaborated using source-separated market waste and urban pruning wastes. After composting, composts C3, C4 and C5 (from Piles 3, 4 and 5, respectively) were used as substrates components, mixed with peat in different percentages (0, 25, 50 and 75%, volume/volume) for seedling production of tomato, courgette and pepper. The composts obtained showed adequate physico-chemical and chemical properties, and a suitable degree of stability and maturity, with absence of phytotoxicity. Regarding their use as growing media, the substrates with 25% (volume/volume) of the compost C3, C4 or C5 had the best properties for their use as substrate components, only C3 reducing the seed germination in the courgette crop. In addition, at an economic level, the alternative of peat substitution at 25% with compost can suppose a reduction of 23% in the cost of the substrate. In the most conservative scenario, this reduction can be of 21%, also with an increase of 2.9% in the business contribution margin. Therefore, composting can be a suitable method not only for the management and recycling of these waste streams, but also for adding value to them, as components of growing media in seedling production. Highlights: Composting is a viable method for urban waste management in Chimborazo (Ecuador). The composts obtained had suitable properties for use as partial substrate component. Substrates with 25% of compost induced good seedling germination and growth.